Effects of Using an Application for Postpartum Contraceptive Use in Family Planning Counseling During Pregnancy - Nurcahyani, Lia; Widiyastuti, Dyah; Iman, Arief Tarmansyah; Cahyati, Yanti; Fitrianingsih, Yeni (UI Scholars Hub, 2023)
A decision-making tool for family planning flipchart is used for contraceptive counseling, but the use of this flipchart is suboptimal. In this study, primary study resulted in innovative decision-making tools for family planning applications. “Si KB Pintar” was also developed, a tool that women can use to discuss contraceptives with their husbands after family planning counseling. This study analyzed the effectiveness of family planning counseling during pregnancy by applying postpartum contraceptive use. Analytical quantitative quasi-experimental methods were used with a control group design. The sampling method was two-stage sampling. In the first stage, from 22 primary health care (PHC) in Cirebon City, Indonesia, 11 intervention and 11 control groups were selected using random allocation. Five participants were taken from each PHC in the second stage using simple random sampling. The findings indicated that participants given family planning counseling using an application had a 2.4 times higher likelihood of using postpartum contraception compared to flipcharts after controlling for age and parity variables. Because these applications are only for Android users, applications should be produced that all users can utilize in further study.